Abnormal Tyrosine Phosphorylation Linked to a Defective Interaction between ADP and Its Receptor on Platelets - Lévy-Toledano, Sylviane; Maclouf, Jacques; Rosa, Jean-Philippe; Gallet, Carole; Vallès, Géraldine; Nurden, Paquita; Nurden, Alan T. (Thrombosis and Haemostasis, 1998)
ADP, a primary stimulus of platelets, binds to one or more populations of receptors on the platelet surface. These receptors are linked to discrete activation pathways. Both G proteins and tyrosine kinases have been implicated in the cellular responses to this agonist. We have studied a patient with a congenital abnormality of ADP-induced platelet aggregation in an effort to gain information on the signalling pathways used by ADP. Immunoblotting with a broadly reactive rabbit antibody recognizing the GTP-binding domain of G protein α-subunits, and with rabbit antibodies specific for Giαl-3, and Gα12 all showed normal reactivity when tested against the patient‘s platelets. The phosphorylation of proteins was studied using an anti-phosphotyrosine MoAb (4G10) and platelets stimulated in a platelet aggregometer with ADP, a thromboxane A2 mimetic (IBOP), TRAP-14-mer peptide and α-thrombin. With normal platelets, a time-dependent phosphorylation of several bands in the 60 to 130 kDa mol. wt. range was observed with all agonists. For the patient, minimal aggregation and little or no phosphorylation of proteins of 80-85 kDa (cortactin), 100-105 kDa and 125-130 kDa were seen in response to ADP. The aggregation and phosphorylation responses were slightly modified in the presence of low doses of thrombin but were normal with high doses. Aggregation and tyrosine phosphorylation were virtually absent with IBOP, a finding reproduced when normal platelets were incubated with IBOP and the CP/CPK ADP scavenging system, thereby underlining the role of ADP in the response to IBOP. Our results show that the ADP receptor pathway deficient in the patient is linked to a selective tyrosine phosphorylation response.